Hubungan Antara Gaya Kepemimpinan Guru Pendidikan Agama Islam dengan Prestasi Akademik Siswa dI SMPN 1 Percut Sei Tuan - Hasibuan, Abdul Fajar; Pulungan, Enny Nazrah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The task of a teacher is not only as an educator but the teacher also plays a role in changing the personality of students for the better. The relationship between the leadership style of Islamic Religious Education (PAI) teachers and student academic achievement can be very significant. The formulation of the problem of this study is to see how the leadership style of PAI teachers in teaching in the classroom and its relationship with improving student academic achievement at school. The purpose of this study was to see how the relationship between the leadership style of PAI teachers and students' academic achievement at SMP Negeri 1 Percut Sei Tuan. This study used a quantitative approach of survey type by using questionnaires to collect information from respondents as a sample. In research with a quantitative approach, the analysis emphasizes numerical data processed by statistical methods. As for the use of sampling techniques, researchers use simple random sampling, namely by making a lottery number to be distributed to students and giving each member of the population the opportunity to be used as a research sample. The results of research related to the relationship between the leadership style of Islamic Religious Education teachers and student academic achievement at SMPN 1 Percut Sei Tuan, namely the leadership style of Islamic Religious Education teachers has a significant relationship with student academic achievement. Seen from the results of the study, researchers found a significant relationship between the leadership style of PAI teachers with students' academic achievement with a contribution of 65.6%.